Gut Lignocellulose Activity and Microbiota in Asian Longhorned Beetle and Their Predicted Contribution to Larval Nutrition - Wang, Lixiang; Li, Chunchun; Wang, Xuan; Wang, Gaijin; Shang, Suqin; Dou, Zhipeng; Luo, Youqing (Frontiers in Microbiology, 2022)
Anoplophora glabripennis (Asian longhorned beetle) is a wood-boring pest that can inhabit a wide range of healthy deciduous host trees in native and invaded areas. The gut microbiota plays important roles in the acquisition of nutrients for the growth and development of A. glabripennis larvae. Herein, we investigated the larval gut structure and studied the lignocellulose activity and microbial communities of the larval gut following feeding on different host trees. The larval gut was divided into foregut, midgut, and hindgut, of which the midgut is the longest, forming a single loop under itself. Microbial community composition and lignocellulose activity in larval gut extracts were correlated with host tree species. A. glabripennis larvae fed on the preferred host (Populus gansuensis) had higher lignocellulose activity and microbial diversity than larvae reared on either a secondary host (Salix babylonica) or a resistant host (Populus alba var. pyramidalis). Wolbachia was the most dominant bacteria in the gut of larvae fed on S. babylonica and P. alba var. pyramidalis, while Enterococcus and Gibbsiella were the most dominant in larvae fed on P. gansuensis, followed by Wolbachia. The lignocellulose-degrading fungus Fusarium solani was dominant in the larval gut fed on different host trees. Functional predictions of microbial communities in the larval gut fed on different resistant host trees suggested that they all play a role in degrading lignocellulose, detoxification, and fixing nitrogen, which likely contribute to the ability of these larvae to thrive in a broad range of host tree species.